2011
DOI: 10.1007/s11242-011-9789-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Network Structure on Characterization and Flow Modeling Using X-ray Micro-Tomography Images of Granular and Fibrous Porous Media

Abstract: Image-based network modeling has become a powerful tool for modeling transport in real materials that have been imaged using X-ray computed micro-tomography (XCT) or other three-dimensional imaging techniques. Network generation is an essential part of image-based network modeling, but little quantitative work has been done to understand the influence of different network structures on modeling. We use XCT images of three different porous materials (disordered packings of spheres, sand, and cylinders) to creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 68 publications
1
40
0
Order By: Relevance
“…The crossover saturation that we identify, S wx = 0.5, should be compared with 0.75, reported by Kiefer et al (2009), while Z = 8 is consistent with the range of connectivities reported by Makse et al (2000), Aste et al (2006), Bhattad et al (2011) andJiang et al (2016) for packings of spheres. As was the case for the drainage, the effect of the PSD and PCD on σ r is negligible.…”
Section: Electrical Conductivity During Imbibitionsupporting
confidence: 89%
“…The crossover saturation that we identify, S wx = 0.5, should be compared with 0.75, reported by Kiefer et al (2009), while Z = 8 is consistent with the range of connectivities reported by Makse et al (2000), Aste et al (2006), Bhattad et al (2011) andJiang et al (2016) for packings of spheres. As was the case for the drainage, the effect of the PSD and PCD on σ r is negligible.…”
Section: Electrical Conductivity During Imbibitionsupporting
confidence: 89%
“…Direct computation using only the pore and throat sizes, assuming cylindrical throats and spherical pores, gives K = 0.0685 × 10 −12 m 2 for the maximal ball network and K = 0.0801 × 10 −12 m 2 for the SNOW network, which is remarkably similar given the differences in the size and density of the pores and throats. This surprising behavior was noted by Bhattad et al [23] and attributed to the increase in the number of flow conduits offsetting the smaller pores. Both of these values are much too low: Dong and Blunt give the experimental value for Berea as K = 0.650 × 10 −12 , which is nearly 10× higher than the model prediction, and the permeability of the image was calculated using the lattice-Boltzmann method as K = 1.286 × 10 −12 , yet another factor of 2 higher.…”
Section: B Berea Sandstonementioning
confidence: 65%
“…This behavior is important since it will alter the size distribution of the network to make it more representative of the real material. Despite Bhattad et al [23] showing that this has surprisingly little impact on the transport properties of the network, researchers will expect physically representative size distributions for comparison to other measurements. The second benefit of this step is that several thin regions that were not caught by the saddle point check are removed.…”
Section: Merging Nearby Peaksmentioning
confidence: 98%
See 1 more Smart Citation
“…A connected line normal to the solid wall of the largest such radii defines the skeleton of the topological network, for both pores and throats [60][61][62][63][64].…”
Section: Pore Extractionmentioning
confidence: 99%